2013
DOI: 10.1093/aje/kws309
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal, Metabolic, and Inflammatory Profiles and Endometrial Cancer Risk Within the EPIC Cohort—A Factor Analysis

Abstract: A "Western" lifestyle characterized by physical inactivity and excess weight is associated with a number of metabolic and hormonal dysregulations, including increased circulating estrogen levels, hyperinsulinemia, hyperglycemia, and chronic inflammation. The same hormonal and metabolic axes might mediate the association between this lifestyle and the development of endometrial cancer. Using data collected within the European Prospective Investigation into Cancer and Nutrition (EPIC), a prospective cohort study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
106
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 127 publications
(107 citation statements)
references
References 38 publications
0
106
0
1
Order By: Relevance
“…High BMI (and hyperadiponectinemia) and non-alcoholic fatty liver may also increase circulating SHBG [70,71]. In our systematic review, only Dossus et al [36] reported the univariable association between SHBG levels and EC and there were no studies reporting fatty liver characteristics. These factors are potential contributors of insulin resistance and endometrial carcinogenesis that should be assessed in future studies.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…High BMI (and hyperadiponectinemia) and non-alcoholic fatty liver may also increase circulating SHBG [70,71]. In our systematic review, only Dossus et al [36] reported the univariable association between SHBG levels and EC and there were no studies reporting fatty liver characteristics. These factors are potential contributors of insulin resistance and endometrial carcinogenesis that should be assessed in future studies.…”
Section: Discussionmentioning
confidence: 72%
“…In addition, hyperinsulinemia may alter the production of insulin-like growth factor-I (IGF-I), may bind to IGF-I receptors and inhibit IGF binding protein-I (IGFBP-I) and thus further contributing to carcinogenesis [72]. Only Dossus et al [36]. evaluated the univariable association between levels of IGFBP-I and -II and EC.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic studies have revealed a strong association between endometrial cancer and insulin resistance (IR) as well as inflammation (4)(5)(6)(7), and inflammation is one of the most significant clinical manifestations of IR (8). In agreement with this clinical finding, macrophage infiltration, a specific manifestation of chronic inflammation, was found to be positively correlated with development of many kinds of cancers, including endometrial cancer (9,10).…”
Section: Introductionmentioning
confidence: 79%
“…Roberts and colleagues brought into the "one system fits all" mechanism three novel candidates: obesityinduced hypoxia, shared genetic susceptibility, and migrating adipose stromal cells [47]. In prospective epidemiological studies, endometrial [48] cancers have been observed in relation to higher levels of circulating C-peptide levels, a biomarker of insulin secretion. In addition, prediagnostic levels of testosterone, androstenedione, dehydroepiandrosterone sulfate, sex hormone-binding globulin, estrone, estradiol, insulin-like growth factor-binding proteins 1 and 2, adiponectin, high-and low-density lipoprotein cholesterol, glucose, triglycerides, tumor necrosis factor (TNF) α, soluble TNF receptors 1 and 2, C-reactive protein, interleukin-6, and interleukin-1 receptor antagonist were measured in 233 incident endometrial cancer cases and 446 matched controls.…”
Section: Obesogenic Environmentmentioning
confidence: 99%
“…In addition, prediagnostic levels of testosterone, androstenedione, dehydroepiandrosterone sulfate, sex hormone-binding globulin, estrone, estradiol, insulin-like growth factor-binding proteins 1 and 2, adiponectin, high-and low-density lipoprotein cholesterol, glucose, triglycerides, tumor necrosis factor (TNF) α, soluble TNF receptors 1 and 2, C-reactive protein, interleukin-6, and interleukin-1 receptor antagonist were measured in 233 incident endometrial cancer cases and 446 matched controls. Factor analysis identified 3 components associated with postmenopausal endometrial cancer risk that could be labeled 'insulin resistance/metabolic syndrome,' 'steroids,' and 'inflammation' factors [48].…”
Section: Obesogenic Environmentmentioning
confidence: 99%